Parental Awareness of Children with Cochlear Implant: Exploring the Positive Experiences of Parents of Children with Cochlear Implant Attending Regular School (Journal of Advances and Scholarly Researches in Allied Education, 2020)
A large number of parents are getting cochlear implants for their children with hearing impairment. This leads to getting their children admitted into regular schools. Since now schools have started taking admissions of children with disabilities it was important to note the parents’ experiences and all that they face in schools. Therefore, present study is conducted on ‘Experiences of parents of children with cochlear implant attending regular school – A Survey’. It is a descriptive survey with purposive sampling. The study collected parental experiences in three major areas – administrative, scholastic and non-scholastic. 30 parents participated in this study whose children used cochlear implant for more than 3 years, were 6 – 16 years in age, attending regular school from minimum 3 years. A questionnaire was developed and validated for the study and was further translated to English, Hindi and Marathi. Questionnaires were responded either through interview method or mail.The overall experiences of parents of children with cochlear implant attending regular school were found to be positive. The study concluded that even though there are several challenges faced by the children with cochlear implant and their parents in a regular school set up, a majority of children were happy according to their parents and the parents were satisfied with their experiences in regular schools.